2013
DOI: 10.1016/j.crohns.2012.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to influenza A/H1N1 vaccine in inflammatory bowel disease patients treated with anti TNF-α agents: Effects of combined therapy with immunosuppressants

Abstract: Background and Aims Our first objective was to evaluate the immune response to the adjuvanted 2009 A/H1N1 pandemic (pH1N1) vaccine in inflammatory bowel disease (IBD) patients treated with anti-TNF-α alone or combined with immunosuppressants (IS). Second and third aims were the safety of pH1N1 vaccine and the effects on IBD clinical activity. Methods 36 patients with Crohn's disease (CD) and 26 with ulcerative colitis (UC) and thirty-one healthy control subjects (HC) were enrolled. 47 patients were on anti T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 37 publications
8
63
0
1
Order By: Relevance
“…A possible exception is the monovalent H1N1 vaccine administered during the 2009 epidemic. Andrisani, et al, found that IBD patients receiving anti TNF-␣ alone or combined with an immunomodulator, mounted a suboptimal immune response to influenza vaccine [23]. This was corroborated by Cullen et al, who found that only 36% of IBD subjects receiving combination immunosuppression were able to achieve seroprotection following the H1N1 vaccine [24].…”
Section: Discussionmentioning
confidence: 83%
“…A possible exception is the monovalent H1N1 vaccine administered during the 2009 epidemic. Andrisani, et al, found that IBD patients receiving anti TNF-␣ alone or combined with an immunomodulator, mounted a suboptimal immune response to influenza vaccine [23]. This was corroborated by Cullen et al, who found that only 36% of IBD subjects receiving combination immunosuppression were able to achieve seroprotection following the H1N1 vaccine [24].…”
Section: Discussionmentioning
confidence: 83%
“…However, when patients are receiving immunosuppressive therapies with combined thiopurines and anti-TNF agents, serologic responses to vaccines are impaired ( 22,23,(43)(44)(45)(46)(47)(48)(49)(50)(51). Nonetheless, even a blunted vaccination response is thought to be of benefi t ( 52 ) and thus recommendations for infl uenza vaccination with inactivated vaccine continue to be broadly applicable to all patients, regardless of immunosuppression status ( 13,53 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…6,7,22 It is unclear if this is also true regarding the monovalent H1N1 vaccine issued in 2009. 8,23,24 It is noteworthy that previous studies defined seroprotection according to humoral response rather than addressing long-term clinical endpoints, such as influenza morbidity.…”
Section: Discussionmentioning
confidence: 98%